Calculability as Politics in the Construction of Markets: The Case of Socially Responsible Investment in France. Issue 4 (April 2016) - Giamporcaro, Stéphanie; Gond, Jean-Pascal
This article examines some of the processes by which power constitutes calculability and, in so doing, shapes the construction of markets. We combine insights from performativity studies about calculability with Lukes' 'radical view of power' to investigate how multiple facets of power are mobilized to influence the creation and activities of calculative agencies in the process of market construction. An in-depth longitudinal study of the French socially responsible investment market shows how organizations acting as calculative agencies become sites of power through calculability. We identify how power is exercised over, through and against these calculative agencies by a variety of actors in order to build their position in the socially responsible investment market. Our results complement the broader question of the 'government of economic life' by showing how micro-level power games interact with the macro-politics of market building through calculative agencies. In so doing, our article sheds light on neglected aspects of the changing geopolitics of calculative power in market construction and suggests approaching 'calculability as politics' when studying the construction of markets.